Differentiation of Yin, Yang and Stasis Syndromes in Severe Aplastic Anemia Patients Undergoing Allogeneic Hematopoietic Stem Cell Transplantation and Their Correlation with Iron Metabolism, cAMP/cGMP, 17-OH-CS and Thyroxine - Hu H (Dove Medical Press, 2021)
Huijin Hu,1,* Tao Chen,2,* Wenbin Liu,1 Yiping Shen,1 Qiushuang Li,3 Yuhong Zhou,1 Baodong Ye,1 Dijiong Wu1 1Department of Hematology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Hematology, Xiaoshan Traditional Chinese Medical Hospital, Hangzhou, Zhejiang, People’s Republic of China; 3Center of Clinical Evaluation and Analysis, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dijiong Wu; Baodong YeDepartment of Hematology, The First Affiliated Hospital of Zhejiang Chinese Medical University, #54 Youdian Road, Hangzhou, Zhejiang, 310006, People’s Republic of ChinaFax +8657187073569Email wudijiong@zcmu.edu.cn; 13588453501@163.comObjective: To better understanding and differentiation of traditional Chinese medicine (TCM) syndromes in severe aplastic anemia (SAA) patients undergoing hematopoietic stem cell transplantation (Allo-HSCT) and their correlation with iron metabolism, cAMP/cGMP, 17-OH-CS and thyroxine.Methods: Eighteen patients with SAA who underwent HSCT were enrolled. The syndrome was evaluated before conditioning and days after stem cell reinfusion (− 10d, − 1d, +7d, +30d, +60d, and +90d). The correlation of TCM syndrome (Yin, Yang, and stasis) to cyclic nucleotides, 17-OH-CS, thyroxine, and iron metabolism were analyzed and compared to data from normal subjects.Results: More “Yin deficiency” (n=11, 11/18) syndrome was observed before HSCT, and nearly 61% was complicated with “blood stasis”. After conditioning, the proportion of “kidney Yin and Yang deficiency” increased to 61.6%. Fourteen days after HSCT, the syndrome developed into “Spleen-Kidney Yang Deficiency,” and the stasis score decreased. On +90day, majority patients were diagnosed with “Kidney Yang Deficiency” (35.7%) or “Spleen-Kidney Yang Deficiency” (28.6%), and 88.9% were diagnosed without stasis. The correlation analysis showed that cGMP might represent “Deficient Yang” as well as low total triiodothyronine (T3) and free T3 (FT3). There was also a positive relation between labile plasma iron (LPI), hepcidin, soluble transferrin receptor (sTfR), and “Yin deficiency”, and the last two factors, along with marrow nitric oxide synthase were also positively related to “Stasis” syndrome.Conclusion: During HSCT, the syndrome evolved from “kidney Yin and Yang deficiency” to “kidney Yang deficiency” or “spleen–kidney Yang deficiency”, and the “stasis” along with “Yin deficiency” syndromes were quickly relieved within 90 days. The changes of cyclic nucleotides, 17-OH-CS, thyroxine, and iron metabolism indexes can be applied for better differentiation of TCM syndrome.Keywords: aplastic anemia, traditional Chinese medicine syndrome, iron metabolism, syndrome evolution, hematopoietic stem cell transplantation